Delphi study to define core clinical outcomes for inclusion in a complex regional pain syndrome international research registry and data bank. Issue 3 (4th March 2023) - Llewellyn, Alison; Buckle, Lisa; Grieve, Sharon; Birklein, Frank; Brunner, Florian; Goebel, Andreas; Harden, R. Norman; Bruehl, Stephen; Vaughan-Spickers, Nicole; Connett, Robyn; McCabe, Candida
Abstract : An electronic Delphi study facilitated consensus on core clinical outcomes for inclusion in a future complex regional pain syndrome international research registry and data bank. Abstract: Complex regional pain syndrome (CRPS) clinical trials have historically captured a diverse range of outcomes. A minimum set of CRPS patient-reported outcomes has been agreed for inclusion in a future CRPS international clinical research registry and data bank. This study aimed to identify a complementary set of core clinical outcomes. Clinicians and researchers from the international CRPS community informed the content of a 2-round electronic Delphi study. Participation was invited from members of the International Association for the Study of Pain CRPS Special Interest Group and the International Research Consortium for CRPS. In round 1, participants rated the relevance of 59 clinical outcomes in relation to the question "What is the clinical presentation and course of CRPS, and what factors influence it?" (1 = not relevant and 9 = highly relevant). In round 2, participants rerated each outcome in the light of the round 1 median scores. The criterion for consensus was median score ≥7, agreed by 75% of respondents. The core study team considered the feasibility of data collection of each identified outcome in agreeing final selections. Sixty respondents completed both survey rounds, with responses broadly consistent across professions. Nine outcomes met the consensus criterion. Final outcomes recommended for inclusion in the core clinical set were record of medications, presence of posttraumatic stress disorder, extent of allodynia, and skin temperature difference between limbs. Study findings provide robust recommendations for core clinical outcome data fields in the future CPRS international clinical research registry. Alongside patient-reported outcomes, these data will enable a better understanding of CRPS.